2008
DOI: 10.1073/pnas.0800272105
|View full text |Cite
|
Sign up to set email alerts
|

Growth/differentiation factor 3 signals through ALK7 and regulates accumulation of adipose tissue and diet-induced obesity

Abstract: Growth/differentiation factor 3 (GDF3) is highly expressed in adipose tissue, and previous overexpression experiments in mice have suggested that it may act as an adipogenic factor under conditions of high lipid load. GDF3 has been shown to signal via the activin receptor ALK4 during embryogenesis, but functional receptors in adipose tissue are unknown. In this study, we show that Gdf3 ؊/؊ mutant mice accumulate less adipose tissue than WT animals and show partial resistance to high-fat diet-induced obesity de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 28 publications
7
139
1
Order By: Relevance
“…This indicates that those phenotypes may be the consequence of deficits in the activities of other ALK7 ligands. We have recently found that GDF-3 signals through ALK7 and regulates accumulation of adipose tissue and diet-induced obesity (14). Although neither Inh␤B Ϫ/Ϫ or Gdf3 Ϫ/Ϫ mutants show signs of reduced insulin sensitivity or liver steatosis (this study and ref.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This indicates that those phenotypes may be the consequence of deficits in the activities of other ALK7 ligands. We have recently found that GDF-3 signals through ALK7 and regulates accumulation of adipose tissue and diet-induced obesity (14). Although neither Inh␤B Ϫ/Ϫ or Gdf3 Ϫ/Ϫ mutants show signs of reduced insulin sensitivity or liver steatosis (this study and ref.…”
Section: Discussionmentioning
confidence: 84%
“…The type I receptor ALK7 can mediate signaling by a selected group of ligands in the TGF-␤ superfamily, including Nodal (12), GDF-1 (13), GDF-3 (14) and activin B (15), all of which can also signal through the ubiquitous activin type I receptor ALK4. Unlike ALK4, however, ALK7 does not mediate activin A signaling (15,16).…”
mentioning
confidence: 99%
“…Given that ATMs are maintained by proliferation 20 , reduction in macrophage frequency in aged VAT may reflect an exhausted senescent-like ATM profile driven by sustained NLRP3 inflammasome activation. The most highly upregulated gene with age, growth differentiation factor-3 ( Gdf3 ), that controls adiposity 21,22 was downregulated upon ablation of Nlrp3 to the levels on par in young mice (Fig. 3b).…”
Section: Main Textmentioning
confidence: 99%
“…4a), suggesting that high levels of GDF3 inhibits lipolysis. Interestingly, age-induced increase of Pcsk6 , which cleaves and activates nodal/ALK7 to promote GDF3 signaling 22 , is also regulated by Nlrp3 (Extended Data 8a). Furthermore, ablation of Gdf3 inhibited the NLRP3 inflammasome activation in BMDMs (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…It is therefore likely that Prkab1, Nek8 (Supporting Information Fig. 3), Ptpr6, Ppp3r, Dlgh3, and Sbk2 are novel and specific regulators of crosspresentation, without significantly affecting MHC class II presentation.We focused on one of the hits, Acvr1c, also known as Alk7, a type I receptor for the TGF-β family of signaling molecules, implicated in the regulation of adipose tissue accumulation [10] and pancreatic β-cell function [11], but no reports on a role in immunity.By measuring protein levels in response to knockdown with different shRNAs, we found a good correlation between Acvr1c protein levels and T-cell proliferation resulting from BMDC antigen cross-presentation (Fig. 1C).…”
mentioning
confidence: 99%